2017
DOI: 10.1136/bmjgast-2017-000160
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs as potential biomarkers to detect transformation of Barrett’s oesophagus to oesophageal adenocarcinoma

Abstract: ObjectiveCirculating microRNAs (miRNAs) are promising biomarkers for the early detection of cancers. This study aimed to address potential circulating miRNAs to monitor the progression from Barrett’s oesophagus (BO) to oesophageal adenocarcinoma (OAC).DesignWe comprehensively analysed tissue and serum miRNA expression profiles of BO mice model (L2-interleukin-1β (IL-1β) mice) using microarray analysis. To validate the data from mice, a published dataset of human plasma miRNAs, consisting of eight patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 62 publications
(38 reference statements)
1
8
0
Order By: Relevance
“…Several studies have analyzed the role of circulating miR-143 as a biomarker in malignant diseases. Just recently, it was demonstrated that patients with acute myeloid leukemia and esophageal adenocarcinoma, disease states which are associated with the activation of immune cells, display decreased serum levels of miR-143 [42, 43], which is in line with our results. Moreover, miR-143 might be directly involved in systemic inflammation and defending bacterial infection.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have analyzed the role of circulating miR-143 as a biomarker in malignant diseases. Just recently, it was demonstrated that patients with acute myeloid leukemia and esophageal adenocarcinoma, disease states which are associated with the activation of immune cells, display decreased serum levels of miR-143 [42, 43], which is in line with our results. Moreover, miR-143 might be directly involved in systemic inflammation and defending bacterial infection.…”
Section: Discussionsupporting
confidence: 92%
“…We [ 36 ] also analyzed tissue and blood miRNAs from human interleukin-1β (IL-1β) transgenic mice (L2-IL-1β mice) as a model of BE. We then compared expression of human plasma miRNAs in eight EAC patients, eight BE patients, and six healthy individuals using a public dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was revealed that miR-141 was involved in the pathogenesis of ulcerative colitis by targeting C-X-C motif chemokine ligand 5 (11). Emerging evidence has previously identified miRs that can be secreted from cells into the extracellular environment, where they are stable and resistant to degradation by RNases (12,13). Circulating miRs are therefore desirable candidates as both endocrine signaling molecules and disease markers (12,13).…”
Section: Introductionmentioning
confidence: 99%